2020
DOI: 10.1007/s11126-020-09796-5
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health During the Covid-19 Outbreak in China: a Meta-Analysis

Abstract: Background: Covid-19 has started to spread within China since the end of December 2019. Despite government's immediate actions and strict control, more and more people were infected every day. As such a contagious virus can spread easily and rapidly between people, the whole country was put into lockdown and people were forced into isolation. In order to understand the impact of Covid-19 on mental health well-being, Chinese researchers have conducted several studies. However, no consistent results were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
159
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(176 citation statements)
references
References 29 publications
10
159
2
5
Order By: Relevance
“…There have been a few published empirical data so far and, instead, the literature is full of opinion papers, viewpoints, perspectives, guidelines and narrations of activities to cope with the pandemic, which borrow from previous experience with pandemics and utilize common sense, but, as a result, often obscure rather than clarify the landscape. A recent meta-analysis reported a 25% anxiety and 28% depression in the general population ( Ren et al, 2020 ) while a second one reported that 29.6% of people experienced stress, 31.9% anxiety and 33.7% depression ( Salari et al, 2020 ). Within the scope of precision and personalized psychiatry, it is important to identify the exact contribution of specific variables to the observed pathology.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a few published empirical data so far and, instead, the literature is full of opinion papers, viewpoints, perspectives, guidelines and narrations of activities to cope with the pandemic, which borrow from previous experience with pandemics and utilize common sense, but, as a result, often obscure rather than clarify the landscape. A recent meta-analysis reported a 25% anxiety and 28% depression in the general population ( Ren et al, 2020 ) while a second one reported that 29.6% of people experienced stress, 31.9% anxiety and 33.7% depression ( Salari et al, 2020 ). Within the scope of precision and personalized psychiatry, it is important to identify the exact contribution of specific variables to the observed pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Although these lockdowns vary in the number and types of measures taken, they usually include certain types of contact restriction as well as the closure of many public meeting places, such as schools, public authorities, and shopping centers. Psychologists, doctors, and other health experts pointed out at an early stage that such interventions in individual lifestyles are likely to be accompanied by psychological consequences, such as increased anxiety or diminished well-being [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Using the draft search strategy of PubMed, EMBASE.com, Web of Science, the Cochrane Library, CBM, CNKI, CQVIP, 146 records were identified, of which 38 duplicates were removed and 108 records proceeded to title/abstract screening. The remaining 35 SRs were retrieved for full text for further eligibility, and 8 SRs [ 11 , 18 , 21 , 23 , 20 , 24 , 27 , 28 ] met the a priori criteria and were included. The PRISMA flow chart of literature section is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%